Genome-Wide Identification and Analysis of the Class III Peroxidase Gene Family in Tobacco (Nicotiana tabacum) - Cheng, Lingtong; Ma, Lanxin; Meng, Lijun; Shang, Haihong; Cao, Peijian; Jin, Jingjing (Frontiers in Genetics, 2022)
Class III peroxidases (PODs) are plant-specific enzymes that play significant roles in plant physiological processes and stress responses. However, a comprehensive analysis of the POD gene family in tobacco has not yet been conducted. In this study, 210 non-redundant POD gene members (NtPODs) were identified in tobacco (Nicotiana tabacum) and distributed unevenly throughout 24 tobacco chromosomes. Phylogenetic analysis clustered these genes into six subgroups (I-VI). Gene structure and motif analyses showed the structural and functional diversity among the subgroups. Segmental duplication and purifying selection were the main factors affecting NtPOD gene evolution. Our analyses also suggested that NtPODs might be regulated by miRNAs and cis-acting regulatory elements of transcription factors that are involved in various biological processes. In addition, the expression patterns in different tissues and under various stress treatments were investigated. The results showed that the majority of NtPODs had tissue-specific expression patterns and may be involved in many biotic and abiotic responses. qRT-PCR analyses of different tissues and stress treatments were performed to verify transcriptome patterns. Expression of a green fluorescent protein-NtPOD fusion confirmed the plasma membrane localization of NtPOD121 and NtPOD4. Furthermore, 3D structures provided evidences of membrane-bound peroxidase. These findings provide useful information to better understand the evolution of the NtPOD gene family and lay the foundation for further studies on POD gene function in tobacco.